The Effect of Internal Auditor Role, Risk Management Function, and Operational Risk Management Supervision on the Performance of Regional Development Bank (BPD) in the Sumatera Region with Information Technology Integration as a Moderating Variable - Kaban, Armin Syahdin; Erlina, Erlina; Hasyim, Sirojuzilam (Dinasti Publisher, 2026)
This study examines the effects of the internal auditor’s role, risk management function, and operational risk management supervision on the performance of Regional Development Banks (BPD) in Sumatra region, with information technology integration serving as a moderating variable. A quantitative approach was employed, involving eight Regional Development Banks and 70 respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The findings reveal that the internal auditor’s role and risk management function do not have a significant effect on bank performance. In contrast, operational risk management supervision has a positive and significant effect on performance. The moderation analysis indicates that information technology integration does not moderate the relationships between the internal auditor’s role and bank performance or between the risk management function and bank performance. However, information technology integration significantly strengthens the positive effect of operational risk management supervision on bank performance. These findings highlight the importance of effective operational supervision and the strategic integration of information technology in enhancing the performance of Regional Development Banks in the Sumatra region.